Efektivitas Pemberian Reward Organisasi dalam Meningkatkan Kinerja Guru di Perguruan Tamansiswa Kota Pematangsiantar - Evri Dahwani Sinaga (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This study aims to determine the effectiveness of providing organizational rewards in improving teacher performance at the Tamansiswa Pematangsiantar College. Rewards that will be examined include material rewards and non-material rewards. Meanwhile, teacher performance includes aspects of planning, implementation, and evaluation. Rewards are consistently applied overall with a proportional nominal value. By giving prizes to teachers who excel, healthy competition will be created between fellow teachers. The results of the study show that the rewards given by the school have no effect on teacher performance. The method used in this study uses a mixed method approach (quantitative mix - qualitative embeded type), namely the qualitative method as the primary method guiding quantitative data as a secondary method carried out in one research phase. The informants in the study were the leadership of the Pematangsiantar Branch of Tamansiswa and several teachers who were randomly selected from all levels of elementary, junior high, high school, and vocational school.